Communication Strategy Environment in Management Trash in The Cottage Ibad Arrahman Islamic Boarding School - Annisa F. Z, Putri; Marthalena, Marthalena (Future Science, 2025)
This research discussing Communication Strategy Environment in Management Trash in the Cottage Ibad Arrahman Islamic Boarding School. Background study based on increasing problem waste produced by 625 residents Islamic boarding school every day with domination rubbish organic up to 92.6%. Problems main issues faced is low awareness students in manage rubbish as well as obstacle internal communication. This research use paradigm interpretive with approach qualitative descriptive. Data collected through observation, interviews, and documentation, then analyzed using Communication Theory Cox Environment 2016. Research results show that communication strategy environment in the Pondok Ibad Arrahman Islamic Boarding School implemented through the Eco Cycle Movement program with utilise religious values, interpersonal approach, lectures, practice direct, as well as simple visual media. The role of the communicator, such as advisor pondok, ustadz, and IKSADA administrators, proven important in build awareness collective. Although however, still there is challenge in the form of low motivation part students, limited communication media, and lack of evaluation sustainable. In conclusion, a systematic, consistent, and data-based communication strategy effective religious-values in increase awareness students, at the same time realize management rubbish sustainable in the environment Islamic boarding school